2022
DOI: 10.1530/ec-21-0425
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor status in the human brain after dexamethasone treatment: a single case study

Abstract: Background: Synthetic glucocorticoids like dexamethasone can cause severe neuropsychiatric effects. They preferentially bind to the glucocorticoid receptor (GR) over the mineralocorticoid receptor (MR). High dosages result in strong GR activation, but likely also lower MR activation based on GR-mediated negative feedback on cortisol levels. Therefore, reduced MR activity may contribute to dexamethasone-induced neuropsychiatric symptoms. Objective: In this single case study, we evaluate whether dexamethasone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
3
1
Order By: Relevance
“…We cannot fully exclude that corticosterone add-on treatment enhanced dexamethasone-induced Fkbp5 and Mt2a expression via additional GR activation, although this is unlikely given the 25-fold higher potency of dexamethasone relative to corticosterone ( 47 ) and our observation that eplerenone fully prevented the additional increase mediated by corticosterone add-on. Because eplerenone decreased the Fkbp5 induction and hyperinsulinemia caused by dexamethasone alone, our data also suggest that dexamethasone at the given dose can act through MR, which is also in line with previous observations ( 17 ). Additional effects of MR activation on top of GR activation involve the binding to common GR response elements (GREs) in target genes, based on the very similar DNA binding domain of MR and GR.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We cannot fully exclude that corticosterone add-on treatment enhanced dexamethasone-induced Fkbp5 and Mt2a expression via additional GR activation, although this is unlikely given the 25-fold higher potency of dexamethasone relative to corticosterone ( 47 ) and our observation that eplerenone fully prevented the additional increase mediated by corticosterone add-on. Because eplerenone decreased the Fkbp5 induction and hyperinsulinemia caused by dexamethasone alone, our data also suggest that dexamethasone at the given dose can act through MR, which is also in line with previous observations ( 17 ). Additional effects of MR activation on top of GR activation involve the binding to common GR response elements (GREs) in target genes, based on the very similar DNA binding domain of MR and GR.…”
Section: Discussionsupporting
confidence: 93%
“…Dexamethasone has a higher affinity for GR than for the MR ( 14 ), which leads to a much higher stimulation of GR in vivo ( 15 ). Since even moderate doses of dexamethasone can completely suppress endogenous GC production, it has been postulated that part of the (central) side effects of dexamethasone may result from MR hypoactivation rather than GR hyperactivation ( 16 , 17 ). Various studies have reported beneficial effects of corticosterone or cortisol add-on treatment on mood, memory and sleep quality in humans and rodents treated with high-dose dexamethasone ( 18 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results published by Zhe and coworkers showed that single-prolonged stress causes a reduced expression of MR and GR in CA1 of the hippocampus [ 32 ]. The differences between our results and those of other studies may be attributed to the dose and duration of GC exposure or other factors that can have different effects [ 10 , 59 ]. Short-term application of both high and low doses of GCs similarly affects GR in cortical neurons by increasing its mitochondrial localization, while during long-term supply, only a high dose decreases GR levels in mitochondria and negatively affects mitochondrial function in neurons [ 10 ].…”
Section: Discussioncontrasting
confidence: 99%
“…30 For synthetic glucocorticoids with a very low MR affinity, this may have consequences for the neuropsychiatric side effects that these drugs may have in some individuals. 6 Drugs such as dexamethasone strongly suppress endogenous cortisol levels and lead not only to extensive GR activation, but also to an under-activation of brain MR. 31,32 In support of the relevance of MR under-activation, a clinical trial in patients with childhood leukemia suggests that co-treatment with low doses of cortisol may ameliorate some of the neuropsychiatric side effects of dexamethasone. 33 The protective effects of MR activation are in line with a series of studies suggesting that a genetic gain of function variant is protective against mood disorders.…”
Section: Binding and Efficacymentioning
confidence: 99%